An Analysis of Conjunctions in Mandarin Comprehensive Textbooks (A Case Study of “Road to Success”): 综合课程教科书中的连词分析——以《成功之路》教科书为例 - Yulia Meiceria; Lily Thamrin; Yoanna Afrimonika (Mandarinable: Journal of Chinese Studies, 2025)
Conjunctions play an important role in clarifying meaning and enhancing communication effectiveness. However, in the context of learning Mandarin as a foreign language, conjunctions tend to receive insufficient attention. This study aims to analyze the use of conjunctions in the first ten volumes of the “Road to Success” textbook series by using a qualitative, combined with descriptive and literature analysis research method. The results recorded a total of 88 conjunctions (73 distinct and 15 repeated), classified into 11 subcategories under two main types: coordinative and subordinative. The most frequently used type were progressive (17), causal (14), and adversative (11) conjunctions, while selective conjunctions were not found in the data. The presentation of conjunction explanations varies across editions. The explanations in the “语法点注释” (grammar points) section are presented systematically and followed by a variety of exercises, reflecting the principle of "concise explanations, extensive practice". Furthermore, the distribution of conjunctions increases progressively, with the highest concentration found in the《进步篇》volume. In alignment with the “Chinese Proficiency Grading Standards for International Chinese Language Education”, the coverage of level 1–4 conjunctions exceeds 50%, with the highest concentration at level 2 (80.9%). These findings indicate that the textbook content is well-aligned with the intended stages of language learning.